Draft Annual Plan 1988-89 Maharashtra State - Planning Commission (Planning Commission, 1987)
The State Government took up the formulation of the Annual Plan 1988-89 in the Introduction background of the guiding principles of the Seventh Five Year Plan and the guidelines issued by the Planning Commission on the subject. A draft Annual Plan of the size of Rs. 2,320 crores has been prepares for submission to the Planning Commission. The Planning Commission has requested the State Government to formulate the Guidelines State’s Annual Plan 1988-89, keeping in view the policies, programmes and thrust areas of for Plan the Seventh Five Year Plan as embodied in the 7th Plan Document.
Government of Maharashtra : Planning Department